Choosing Wisely Campaign – Innovations in Cardiovascular Science and The United States Healthcare System - Rehman, Hiba (Cureus, 2018)
The United States (US) is the third most expensive health care system in the world, but despite that, the US ranked last in the top 50 countries of the world when it comes to the performance measures, such as healthcare efficiency, life expectancy, health care costs, and gross domestic product (GDP) percentage. The spending health care cost keeps increasing and most of the healthcare costs go to waste. Due to this reason, it is therefore extremely important to focus on improving the quality and to bring the costs in appropriate control. To avoid this issue, the Choosing Wisely Campaign (CWC) came into being in 2012. The CWC encourages discussions between providers and patients regarding the care based on the evidence base, free from harm, duplicative or redundant tests/procedures that the patient already received, and whether medications, tests, or procedures are really necessary. Although diagnostic tests or procedures are highly valued for decision-making, unnecessary testing creates harmful health services and an economic impact on the healthcare system. The CWC has spread widely throughout the world but has many challenges which are limiting the CWC in further adoption and spread in the US. To overcome challenges in implementing and spreading the CWC, the government, physicians, social media, and mass media play an important role.